Holistic Curriculum Development in Islamic Religious Education Institutions in Primary Schools or Madrasah Ibtidaiyah - Anati Rahila; Khozin (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
The era has experienced developments and changes in various fields. These developments and changes can affect changes in the education system. Nowadays, education has become an important part of social life, because education can change the quality of one's life. It can be proven that the higher the level of education, the more knowledge and experience a person has so that it is easier to solve life problems. One of the cornerstones of education is the curriculum, so when there are developments in various fields that can affect the education system, the curriculum is the same. Problems that arise in society also encourage changes in the education system. The curriculum is here to solve problems and meet the demands of society. The curriculum is designed to facilitate existing learning. This research uses qualitative research methods with the type of library study (library research), which is a method of collecting data by understanding and studying theories from various literature related to research, collecting data by searching for sources and reconstructing from various sources such as books, journals, and existing research. The indicators of success include understanding the concept of Islam, applying the values of religious teachings in daily life, improving student behavior and attitudes, and improving the quality of individual character Developing a holistic curriculum for Islamic religious education in elementary schools or madrasah ibtidaiyah is an important step in developing balanced and moral individuals. This curriculum covers the development of all aspects of a person, including physical, mental, emotional and spiritual. The implementation of a holistic curriculum requires the active role of teachers and the application of creative and interactive learning methods. The success of a holistic curriculum can be seen from the achievements of students in understanding religious concepts, applying religious education values, changing behavior and improving the quality of individual character. By developing a holistic curriculum, it is hoped that Islamic religious education can contribute to the formation of a pious national character.